The long and the short of it: Russian predicate adjectives with zero copula. - Nesset, Tore; Janda, Laura A. (Russian Linguistics, 2023)
The present article presents an empirical investigation of the choice between so-called long (e.g., prostoj 'simple') and short (e.g., prost 'simple') forms of predicate adjectives in Russian, based on data from the syntactic subcorpus of the Russian National Corpus. The data under scrutiny suggest that short forms represent the dominant option for predicate adjectives. It is proposed that long forms are descriptions of thematic participants in sentences with no complement, while short forms may take complements and describe both participants (thematic and rhematic) and situations. Within the "space of competition" where both long and short forms are well attested, it is argued that the choice of form to some extent depends on subject type, gender/number, and frequency. On the methodological level, the approach adopted in the present study may be extended to other cases of competition in morphosyntax. It is suggested that one should first "peel off" contexts where (nearly) categorical rules are at work, before one undertakes a statistical analysis of the "space of competition".